2015
DOI: 10.1371/journal.pone.0134846
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Lipid Accumulation in Chlorella vulgaris via Flow Cytometry and Liquid-State ¹H NMR Spectroscopy for Development of an NMR-Traceable Flow Cytometry Protocol

Abstract: In this study, we cultured Chlorella vulgaris cells with a range of lipid contents, induced via nitrogen starvation, and characterized them via flow cytometry, with BODIPY 505/515 as a fluorescent lipid label, and liquid-state 1H NMR spectroscopy. In doing so, we demonstrate the utility of calibrating flow cytometric measurements of algal lipid content using triacylglyceride (TAG, also known as triacylglycerol or triglyceride) content per cell as measured via quantitative 1H NMR. Ensemble-averaged fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In the context of microalgae, NMR spectroscopy has been used to determine their chemical composition using diverse technical implementation to show lipophilic [55][56][57] and hydrophilic [55,57,58] compounds or the whole cells profile [55,59,60]. The usefulness of NMR spectroscopy for microalgae classification has been also demonstrated, showing the changes in the profiles of different microalgae classes [61].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of microalgae, NMR spectroscopy has been used to determine their chemical composition using diverse technical implementation to show lipophilic [55][56][57] and hydrophilic [55,57,58] compounds or the whole cells profile [55,59,60]. The usefulness of NMR spectroscopy for microalgae classification has been also demonstrated, showing the changes in the profiles of different microalgae classes [61].…”
Section: Introductionmentioning
confidence: 99%
“…Both FSC and SSC were impacted by 5AZA treatment in similar ways: initially 5AZA significantly increased both FSC ( Figure 5D, p < 0.01) and SSC ( Figure 5E, p < 0.001) until Days 8 and 10, respectively, but this effect was abrogated as the days in culture increase. In other studies of microalgae cultivation, lack of change in cell counts accompanied by an increase optical density, FSC, and SSC suggests altered cellular composition particularly of biomolecules like neutral lipids (Bono et al, 2015;Gonzalez-Esquer et al, 2019;Steadman Tyler et al, 2019). Using a BODIPY fluorescent probe (Steadman Tyler et al, 2019), we found that lipid accumulation was significantly increased after 4 days of 5AZA treatment (Figure 5F).…”
Section: Aza Treatment Altered Cellular Characteristics and Biomolecmentioning
confidence: 51%
“…BODIPY 505/515 has been the fluorescent marker of choice for the evaluation of intracellular lipids in algae [166,168]. TAG content in BODIPY 505/ 515-stained C. vulgaris by single-cell fluorescence strongly correlated with the result obtained by 1 H NMR [126]. BODIPY 505/515 dissolved in DMSO at a final concentration of 1-10 μM was shown to selectively stain lipid bodies of several taxa of live algae.…”
Section: Fluorescence Spectroscopymentioning
confidence: 69%
“…This strategy was applied to quantify TAGs in living microalgae in their growth medium [125]. NMR is ideal for high-throughput calibration of flow cytometry methods aimed at the quantification of cellular TAGs in various algal species [126]. Further, semi-solid NMR techniques, such as high-resolution magic-angle spinning (HR-MAS) and intermolecular multiple-quantum coherence (iMQC), can be used to detect non-TAG lipids [126].…”
Section: Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation